A Study of Metacognitive Knowledge and Metacognitive Regulation among Biology Teachers at Secondary Level - Saima Aamir, Qudsia Riffat (JSE, 2023)
Metacognition is a higher-order thinking construct involving the control of cognition for effective learning. Metacognition has an important role in education because it can make the learner more involved in the learning process. Therefore, it is important to develop metacognitive awareness in students as well as teachers. The current study aimed to measure metacognitive knowledge and metacognitive regulation of Biology teachers at the secondary level. T